Tephra deposits and carbon dynamics in peatlands of a volcanic region: Lessons from the Hekla 4 eruption. (25th September 2020) - Möckel, Susanne C.; Erlendsson, Egill; Prater, Isabel; Gísladóttir, Guðrún
Abstract: Interactions between tephra deposits from volcanic eruptions and peatland carbon (C) dynamics are poorly understood despite the significant extent of peatlands influenced by tephra worldwide. Tephra falls can affect peat accumulation within a radius of at least 1, 000 km. In Iceland, volcanic activity is amongst the highest in the world and it might even increase due to pressure release on subglacial volcanoes. A potent combination of sparse vegetation, low cohesion of Andosols, and frequent strong winds, facilitates the regular input of mineral aeolian material from eroded areas into peatlands in Iceland, in addition to tephra deposits. We present results of a study on the impact of a major tephra deposit, the Hekla 4 tephra, on C dynamics in Icelandic peatlands. We investigated three sites at differing distances from the active volcanic zones and major erosion areas in the interior of the country. A combination of variables was applied, including laboratory C mineralization at 5, 15 and 25°C and C structure obtained by solid‐state 13 C NMR spectroscopy. Tephra deposits seem to affect C dynamics. Differences in C mineralization can only be partially explained by C structure. The C mineralization from soils with conspicuously similar C structure differs by a factor of up to 2.7. Temperature sensitivity of decomposition after the tephra deposition increases by a factor of up to 2.2. Changes in inorganic matter and the ratio of soil organic matter to soil organic carbon by a factor of up to 1.3 and 1.4, respectively, were also observed.